ALMANCA VE TÜRKÇE’DEKİSESTEŞKELİMELER VE BU KELİMELERİN HER İKİDİLDEKİ KARŞILIKLARI VE FONKSİYONLARI - Aygün, Mehmet (Selcuk University, 2007)
Bu çalışmada, Türkçe ve Almanca’daki sesteş eşsesli kelimeler ve bunların kullanımlarımukayese edilmişve her iki dildeki anlamlarıverilmeye çalışılmıştır. Çalışmanın sonunda, her iki dilde benzer yazılışıolan kelimeler bazen aynıkelime bazen de farklıbir kelime şeklinde kullanılmışlardır. Bu kelimeler, Türkçe yada Almanca’da diğer dildekinden farklıkelime şeklinde olmalarına rağmen bazen aynımanada bazen de farklıanlamda kullanılmaktadırlar. Bu kelimelerin çoğu isim olarak kullanılmakta ve bunların çoğu farklıdillerden alınmıştır.

In this study, the homonym words and their use in Turkish and German are compared and their meanings in both languages are tried to be given. At the end of the study the words which have the similar spelling in both languages are sometimes used as the same word type and sometimes as the different word type. These words are sometimes used in the same meaning and usually in different meaning even though in either German or Turkish may belong to the different word types in the other language. Many of these words are used as nouns and most of these words are borrowed from different languages